2016
DOI: 10.1111/cid.12449
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Loading of Fixed Complete Denture Prosthesis Supported by 4–8 Implants Placed Using Guided Surgery: A 5‐Year Prospective Study on 66 Patients with 356 Implants

Abstract: immediately loaded implants placed in edentulous patients using computer-assisted template-guided surgery to support a FCDP is a valid treatment concept in the medium term follow-up, for edentulous patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 31 publications
1
33
0
1
Order By: Relevance
“…This makes it difficult to evaluate how the present results were consistent with other comparable studies. Nevertheless, recent independent studies reported similar results in three-dimensional deviation between virtual planning and final implant positions [10,11,12]. …”
Section: Discussionmentioning
confidence: 59%
“…This makes it difficult to evaluate how the present results were consistent with other comparable studies. Nevertheless, recent independent studies reported similar results in three-dimensional deviation between virtual planning and final implant positions [10,11,12]. …”
Section: Discussionmentioning
confidence: 59%
“…The insertion of dental implants by means of computer‐assisted template‐based surgery is an established method . One of the most important stages for the development of guided implant placement has been the diffusion of 3‐dimensional imaging technique and modern implant planning softwares . The increased demand for dental implants to replace teeth has encouraged advancement in digital technology to improve patients' acceptance and clinical outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the dual acid etched surface of these implants has the potential to accelerate bone healing, as demonstrated by a recent histologic/histomorphometric human study [13]. In modern oral implantology, the presence of an adequate macrostructure (thread design) and microstructure (surface roughness) is considered critical for functional immediate loading [21][22][23]. Finally, new materials (such as composite resins) are now available for the fabrication of fixed full arch mandibular dentures [24,25].…”
Section: Discussionmentioning
confidence: 99%